DEPOSITION Ti-Sn ON AISI 316L SUBSTRATE WITH SURFACE MECHANICAL ALLOYING TREATMENT (SMAT) FOR BIOMATERIAL APPLICATION IN SIMULATED BODY FLUID - Pangestu , Febriyanto Wijaya; D. , Talitha Ratna; Prajitno , Djoko Hadi (Deputi TIRBR-BPPT, 2020)
The properties of biomaterials such as biocompatibility, which is non-allergic and non-toxic to be the main requirements that must be owned by the biomaterials because of the presence of direct contact between the biomaterial with body parts. Therefore the study of biomaterials is constantly carried to repair the biocompatibility. In this research, the improvement of the properties the compatibility of the metal alloy AISI 316L with superimposed ideal bio-inert Ti-Sn with the method of Surface Mechanical Alloying Treatment. Manufacture of the alloy with bio-inert Ti-Sn using a variation of the composition of Sn of 10% and Sn 20% done using Mechanosynthesis process. The results of the process are sintered with the variation of temperature of 800oC and 900oC for 2 hours and then were characterized by an optical microscope. Corrosion testing of the alloy was carried out with Polarization Tafel System Three Electrode method for 10 minutes. The results of characterization with an optical microscope shows there is a layer of bio-inert Ti-Sn the results of the process of SMAT of AISI 316L. The results of corrosion testing on alloy AISI 316L Ti-Sn in a solution of SBF showed that the content of Ti-10%Sn with a temperature of 800oC the obtained corrosion rate 4.785 MPY and at 900oC amounted to 4.155 MPY as well as on the content of Ti-20%Sn with a temperature of 800oC the obtained corrosion rate 3.525 MPY and at 900oC amounted to 3.234 MPY. Keywords: Biocompatible; Biomaterial; AISI 316L; Ti-Sn; Corrosion Rate; Allergic Reaction;Â Deposition.